PHACTR1 regulates oxidative stress and inflammation to coronary artery endothelial cells via interaction with NF-κB/p65. (November 2018) - Zhang, Zhihui; Jiang, Fenglin; Zeng, Lixiong; Wang, Xiaoyan; Tu, Shan
Abstract: Background and aims: Genome-wide association studies have showed that genetic variants in phosphatase and actin regulator 1 ( PHACTR1 ) are associated with coronary artery disease and myocardial infarction. However, the underlying mechanism of PHACTR1 in atherosclerosis remains unknown. Methods: Immunoblots were performed to evaluate the expression of PHACTR1 and phosphorylation of NF-κB signaling. Reactive oxygen species (ROS) labeled with DCFH-DA were assessed by flow cytometry. Fluorescence microscope was used to detect the translocation of p65 in human coronary artery endothelial cells (HACECs). Co-immunoprecipitation was performed to determine the interaction of PHACTR1 with MRTF-A. Results: The mRNA and protein levels of PHACTR1 were markedly increased in carotid plaquescompared with normal carotid arteries. Immunofluorescence staining indicated that PHACTR1 was constitutively expressed in endothelial cells in carotid plaques. Knockdown of PHACTR1 reduced excessive ICAM-1, VCAM-1 and VE-cadherin expression induced by oxidized low density lipoprotein (ox-LDL) in HCAECs. Additionally, silencing PHACTR1 alleviated p47phox phosphorylation and intracellular oxidative stress reflected by the reduction of ROS. Molecular experiments revealed that knockdown of PHACTR1 attenuated NF-κB activity without affecting IκBα and IKKα/β phosphorylation. In contrast, nuclear translation of p65 was blocked by depletion of PHACTR1. Furthermore, co-immunoprecipitation showed that PHACTR1 interacted with MRTF-A and p65 in HCAECs. Knockdown of MRTF-A suppressed the interaction of PHACTR1 with p65, subsequently blocking the nuclear translocation of p65. Conclusions: Our finding suggest that silencing PHACTR1 alleviates the nuclear accumulation of p65 and NF-κB via interaction with MRTF-A, ensuing attenuating oxidative stress and inflammation in HCAECs. Highlights: Genome-wide association studies have identified that genetic variants in phosphatase and actin regulator 1 (Phactr1) are associated with the incidence of coronary artery disease and myocardial infarction. Inspired by these epidemiological data, we determined the role of Phactr1 on endothelial dysfunction for the first time. In this regard, our finding suggested that silencing Phactr1 alleviated the nuclear accumulation of p65 and NF-κB via interaction with MRTF-A, attenuating inflammation and monocyte adhesion in HCAECs. These results, for the first time, decipher the mechanisms underlying the effect of Phactr1 on vascular endothelium dysfunction and might provide insights into the biological underpinnings of genetic variants within Phactr1 in CAD and MI patients.